Patient Satisfaction with Clinical Laboratory Services and Related Factors among Patients Attendance in Outpatient Departments - Abdulatif Turkistani,; Yasser Qattan,; Manal Ali Alshihri,; Khadija Hassan Hussein Al-Momen,; Ahmed Mohammed A Bakhder,; Abeer Rakan Alenazi,; Ahmed Abdulqader Hafez,; Hamza Ahmad Banafi,; Naseem Wasil Allah Hammoud Al-Thubaiti,; Abdulaziz Yahya Al-shahrani,; Fahad Abdulaziz Alabbas, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The quality of laboratory services is a fundamental component of healthcare delivery, as laboratory tests help diagnose, monitor, and manage medical conditions. In Saudi Arabia, clinical laboratories play a crucial role in supporting outpatient care, especially in diagnosing common illnesses, chronic diseases, and conditions requiring specialized attention. As part of the Kingdom’s Vision 2030, the Saudi government has emphasized the improvement of healthcare services, including laboratory diagnostics, to enhance overall health outcomes and patient satisfaction. The study aims:To assess patient satisfaction with clinical laboratory services and related factors among patients attendance in outpatient departments at Jedahh hospital, KSA. Cross-sectional study was conducted among 391 patients from March to May, 2024 using interviewer-administered questionnaire. Systematic random sampling technique was used. Data were entered into Epi-Data software version 4.2, and analyzed using SPSS 28.0. Binary logistic regression analysis was employed. Variables having p-value < 0.05 were considered as statistically significant. Results: Overall level of patient satisfaction towards clinical laboratory services was 48.3%. Patients with no occasion of missing laboratory results [AOR: 2.10; 95% CI (1.13, 3.83)], had diplomas and above educational level [AOR: 0.38; 95% CI (0.15, 0.96)], and who reported no place in the laboratory to put personal things [AOR: 0.37; 95% CI (0.21, 0.54)] were significant factors. Hospital administration and laboratory department in hospital should strengthen their effort to improve patient satisfaction focusing on educational status of patients, missing laboratory results, and the availability of places to put personal things in the blood drawing room.